Physical aggression in early childhood : bridging the gap between theory and practice : a thesis presented in partial fulfilment of the requirements for the Master of Educational Psychology at Massey University, New Zealand - Jones, Sarah (Massey University, 2012)
Literature reviewed in this study suggested there is a gap between recommendations made in research for supporting children with physically aggressive behaviour and the actual experiences of early childhood teachers working with these children. The aim of this study was to identify how early childhood teachers can be provided with greater knowledge and resources to effectively support young children with physically aggressive behaviour. A mixed methods design was chosen for this study. Data collection included interviews with five head teachers from early childhood centres across Taranaki and survey responses from a random sample of four centres across the region. Interview and survey data was subjected to thematic and content analysis and revealed a number of early childhood teachers would like access to greater knowledge and resources to support children with physically aggressive behaviour and their families. Early childhood teachers expressed an interest in access to guidelines to inform their practice and greater awareness of what support is currently available. Teachers also made explicit the need for relevant professional development which provides specific strategies for managing physically aggressive behaviour. The findings of this study suggest early childhood teachers need increased education and knowledge to effectively meet best practice for these children and their families.
Keywords: Aggressive children; Problem children; Preschool education; Early childhood education; Classroom management; Behaviour modification; New Zealand